The Influence of Achievement Motivation on Employee Performance at PT. Surya Rengo Containers Karawang Outsourcing Section 2024 - Taufikˡ, Indri Shahidah; Ismuni, Mutdi; Audina, Bella Puspita (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
Motivation is the force that motivates individuals to contribute to the best of their ability to ensure that the company succeeds in achieving its goals. Basically Motivation is a state within a person that stimulates the desire to perform a certain task in order to achieve a specific goal. This research focuses on the goal of determining the level of professional participation. Ability Motivation and the impact of competency incentives on professional performance in PT container Surya Rengo. The research conducted in this study is quantitative in nature. The sample population was analyzed using organizational research methods, consisting of 60 students. The results showed that the correlation coefficient (r) obtained was 0.740, indicating that competency motivation has a significant positive effect on performance. employee Achievement motivation supports 54.7% of employee engagement in PT Surya Rengo Containers Karawang, while the remaining 45.3% is affected by other factors. There is a significant relationship between performance motivation and employee performance in PT Surya Rengo Containers Karawang as the statistical t-value (8,372) is higher than the t-table value (2,000), which leads to the acceptance of H1 and Rejection of H0